The Rising Conflict for Democracy in the Arab World - Nagi, Farouk S. (URJ-UCCS: Undergraduate Research Journal at UCCS, 2008)
"Operation Freedom" in Iraq has started what could be called the "fourth wave of democracy", a process that happens when success of democracy in one country causes other countries to democratize. Since democracy plays such an important role in the Arab world, it is important to understand how far democracy has come in the Arab world. This paper examines whether or not democracy currently exists, the current progression of democratization, and the Arab peoples call for democratic change. The paper examines authoritarian regimes' arguments of legitimacy and freedom of elections, the regime as a source of stability in the region, and the encouragement of democratic reforms. This study reviews research from the past three decades. This study examines Tunisia, Libya, Yemen, Egypt, Syria, Jordan, Algeria, and Saudi Arabia with the intent of evaluating progressive democratization. Preliminary findings indicate that Arab peoples are challenging current systems and calling for democratic change. These results are important to acknowledge because they indicated the beginnings of a democratic revolution in the region, proving that Arab peoples have a better sense of what changes can be made to help them become more democratic.